Bienestar espiritual y resiliencia en estudiantes de Psicología de una universidad privada de Juliaca - Coaquira Masco, Percy (2025)
The objective of this research is to determine if there is a significant relationship between spiritual well-being and resilience in psychology students from a private university. The type of research belongs to a non-experimental, cross-sectional, correlational and quantitative approach design. In the present study, 173 students participated, who were selected through probabilistic sampling for convenience, taking into account men and women. The instruments used were the Spiritual Well-Being Scale and the Resilience Scale, which present validity and reliability. The findings allow us to observe that spiritual well-being and resilience are positively and statistically significantly correlated (rho= .561; p> .05). Moreover, it was found that spiritual well-being and the dimensions of resilience equanimity (rho= .486; p> .05), personal satisfaction (rho= .525; p> .05), feeling good only (rho= .556; p> .05), self-confidence (rho= .528; p> .05) and perseverance (rho=.559; p> .05) were correlated positive and significantly.